2020
DOI: 10.3389/fimmu.2020.588382
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Facilitates Chikungunya Virus Infection by Inhibiting IFN-α2 Expression

Abstract: Interferons (IFNs) are the key components of innate immunity and are crucial for host defense against viral infections. Here, we report a novel role of interleukin-17A (IL-17A) in inhibiting IFN-α2 expression thus promoting chikungunya virus (CHIKV) infection. CHIKV infected IL-17A deficient ( Il17a −/− ) mice expressed a higher level of IFN-α2 and developed diminished viremia and milder footpad swelling in comparison to wild-type (WT) control mice, which was also recapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 78 publications
5
20
1
Order By: Relevance
“…Likewise, no differences in viral RNA load were found in the feet or muscle of mice treated with anti-IL-17A/F compared to that of isotype-treated mice at 3 dpi and 10 dpi, although a modest reduction was observed in the feet and muscle of mAb-treated mice at 3 dpi and 10 dpi, respectively ( Fig 6D ). In light of these data, and previous reports showing that in CHIKV infection, mice deficient in IL-17 signaling displayed an increase in Type I IFN responses that was associated with reduced viral burden [ 64 ], we asked whether anti-IL-17A/F treatment was also associated with enhanced, early Type I IFN transcriptional responses in the tissues. At 3 dpi, we observed no significant differences in IFNβ mRNA expression in the feet and muscle ( Fig 6E ).…”
Section: Resultsmentioning
confidence: 94%
“…Likewise, no differences in viral RNA load were found in the feet or muscle of mice treated with anti-IL-17A/F compared to that of isotype-treated mice at 3 dpi and 10 dpi, although a modest reduction was observed in the feet and muscle of mAb-treated mice at 3 dpi and 10 dpi, respectively ( Fig 6D ). In light of these data, and previous reports showing that in CHIKV infection, mice deficient in IL-17 signaling displayed an increase in Type I IFN responses that was associated with reduced viral burden [ 64 ], we asked whether anti-IL-17A/F treatment was also associated with enhanced, early Type I IFN transcriptional responses in the tissues. At 3 dpi, we observed no significant differences in IFNβ mRNA expression in the feet and muscle ( Fig 6E ).…”
Section: Resultsmentioning
confidence: 94%
“…Further, studies have reported that the expression of OGT and OGA is sensitive to fluctuations at cellular GlcNAc levels, and cells can coordinate their expression to buffer themselves from drastic shifts in glycosylation [60][61][62][63]. Further, the mutation in Hexa has also been linked with a congenital disorder in humans, Tay Sachs disease, in which the growth and development of the brain is inhibited [64]. In this study, we inhibited the expression of Hexa in Vero cells by using Z-Pugnac or siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive neutrophil recruitment is seen in the lungs of patients diagnosed with either severe IAV infection or severe SARS-CoV-2 [ 87 , 88 , 89 ]. Type I IFNs have been shown to suppress neutrophil-mediated pathologies in both chikungunya virus (CHIKV) and IAV infection in mice by regulating their recruitment to the site of infection [ 11 , 63 , 90 , 91 ]. Neutrophil recruitment in the absence of IFNAR was dependent on increased CXCL1 production by Ly6C int monocytes in IAV infection and CXCL2 expression by monocytes in epicutaneous HSV-1 infection [ 11 , 64 ].…”
Section: The Role Of Interferon and Aging In Regulating The Innatementioning
confidence: 99%
“…Heightened viral replication due to a deficit in type I IFN signaling in conjunction with increased IL-17 signaling can synergize to enhance neutrophil-mediated pathologies during infection [ 62 ]. Interestingly, Neupane et al recently showed that IL-17A inhibited IFN-α2 production and the expression of ISGs during CHIKV infection by downregulating the expression of Irf5 and Irf7 in both structural and myeloid-derived cells, including bone marrow-derived macrophages and DCs [ 91 ]. Despite the reduction in the chemotactic ability of neutrophils seen in aged mice, these deficits are offset by the increased IL-17A production by aged NKT cells, as well as the increased production of the typical neutrophil-attracting chemokines, CXCL1 and CXCL2, in MCMV and HSV-2 systemic infection, resulting in liver injury [ 61 , 62 ].…”
Section: The Role Of Interferon and Aging In Regulating The Innatementioning
confidence: 99%